Exploring the biochemical, haemostatic and toxinological aspects of mapanare dry-tail (Porthidium lansbergii rozei) snake´s venom causing human accidents in Eastern Venezuela - Girón, María E.; Ramos, María I.; Cedeño, Luisneidys; Carrasquel, Axl; Sánchez, Elda E.; Navarrete, Luis F.; Rodríguez-Acosta, Alexis (Investigación Clínica, 2018)
Ver Resumen PDF.